A quantitative analysis of the relationship between drivers of innovativeness and performance of MSMEs. (2015) - Gupta, Himanshu; Nanda, Tarun
This paper investigates the relationship between various drivers of innovativeness and various performance indicators of Micro, Small and Medium Enterprises (MSMEs). The empirical evidence is based on quantitative data gathered through a questionnaire which yielded 65 qualified responses from the representatives of Punjab's small and medium cutting tool and automotive component manufacturers. The analysis of the responses is based on the descriptive analysis of key issues under each input factors. The empirical evidence validates some of the theoretical findings and indicates a strong correlation between entrepreneur role and various research outputs. But analysis of the results indicates poor correlation between linkage capability and regulatory corroboration with research outputs thus underlining the need for government to reach out to MSMEs of the region and extend various programmes run by them to MSMEs so that they can avail these benefits and develop, also there is need for manufacturing organisations to form alliances with other small-scale organisations, large enterprises as well as with institutes and universities for technology transfer and acquiring technical competencies.